An Analysis of Students’ Motivation in Learning English During Pandemic Covid-19 at the Seventh Grade of SMPN 1 Bukit Batu - Mashitah Mashitah; Kurniati Kurniati; Ervina Ervina (Akademika: Jurnal Keagamaan dan Pendidikan, 2022)
This research is motivated by most of the students have low participation in learning English during pandemic COVID-19. The aim is to know Students' intrinsic motivation and Students’ extrinsic motivation in learning English during pandemic COVID-19. The method used is a survey method with a quantitative descriptive approach. The subjects of this research are the students of seventh grade of SMPN 1 Bukit Batu in the academic year of 2021/2022. The sampling technique used is simple random sampling, the researcher takes the sample using lottery so that this study used 86 students to be used as samples. The data in this study were obtained by distributing questionnaires in the form of statements using a Likert scale. Data analysis techniques using descriptive statistics. The results of this study show that 1) The average level of students' intrinsic motivation in learning English during the pandemic COVID-19 is in the excellent category. 2) Average level of students' extrinsic motivation in learning English during the pandemic COVID-19 in the Good category